What you have to know about Human Milk Oligosaccharides - Vassilios Fanos; Alessandra Reali; Maria Antonietta Marcialis; Flaminia Bardanzellu (Hygeia Press di Corridori Marinella, 2018)
Human Milk Oligosaccharides (HMOs), the third most important solid components of BM (the first and the second being lactose and lipids respectively), are a highly variable family of unconjugated glycans related to many pathophysiological short- and long-term effects on infants and, as recently demonstrated, even on the mother. Among their functions are promotion and modulation of gut microbiota, effects on intestinal mucosa and its development, protection against intestinal or extra-intestinal infections, modulation of several immune responses and even extra-intestinal effects, such as brain development, as described in literature. Regarding HMOs composition, it appears that maternal genetic factors play the major role in conferring its high and peculiar inter- and intra-individual variability to BM. HMOs greatly depend on four maternal phenotypes, defined depending on the expression of two specific genes and maternal blood group. The α-1-2-fucosyltransferase (FUT2) gene, expressed in more than 70% of Caucasian women, is codified by the Se gene and allows classification of secretor (Se+) and non-secretor (Se-) mothers. In addition, the α-1-3-4-fucosyltransferase (FUT3) gene indicates positivity or negativity for the Lewis Group (Le+ or Le-). Even other environmental and maternal factors, represented by age, diet, health status, medication and drugs appear to play a role in HMOs composition.